2017
DOI: 10.3389/fimmu.2017.00354
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Improves Immunity and Disease Resistance in Rabbits

Abstract: Probiotics such as Lactobacillus and Bifidobacterium have been successfully used to promote growth and prevent diseases. Previous reports have demonstrated that Bacillus subtilis (B. subtilis) was a potential probiotic for animals. In this research, 180 B. subtilis were isolated from the soil, identified, and investigated in vitro. Furthermore, five B. subtilis were selected and mixed to investigate their effect on growth performance, immune response, intestine microbiota, and disease resistance in rabbits. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(163 citation statements)
references
References 45 publications
5
147
1
1
Order By: Relevance
“…The correlation analysis showed that the relative abundances of Lachnospiraceae_XPB1014_group, Rikenellaceae_RC9_gut_group, Ruminococcaceae_UCG-002 and Prevotella_2 were negatively correlated with serum IgG content; the lower abundances of these genera triggered by CPB addition indicated that CPB was able to increase host immunity, corresponding with the high serum IgG concentration caused by CPB administration. The previous report showed that probiotics could increase host serum IgG levels [30,31], in agreement with this study. This study demonstrated that oral administration of CPB enhanced host intestinal homeostasis by modulating the composition of gut microbiota for improving piglet production performance.…”
Section: Discussionsupporting
confidence: 93%
“…The correlation analysis showed that the relative abundances of Lachnospiraceae_XPB1014_group, Rikenellaceae_RC9_gut_group, Ruminococcaceae_UCG-002 and Prevotella_2 were negatively correlated with serum IgG content; the lower abundances of these genera triggered by CPB addition indicated that CPB was able to increase host immunity, corresponding with the high serum IgG concentration caused by CPB administration. The previous report showed that probiotics could increase host serum IgG levels [30,31], in agreement with this study. This study demonstrated that oral administration of CPB enhanced host intestinal homeostasis by modulating the composition of gut microbiota for improving piglet production performance.…”
Section: Discussionsupporting
confidence: 93%
“…Crucially, integration of the expression systems into the genomes of the engineered microorganisms will help diminish the spreading of antibiotic resistant genes to pathogens via the plasmids. To address further safety concerns, we envision that the platform could be adapted to other microorganisms that previously demonstrated their innocuity for humans, and were used in other animal models for synthetic biology applications, such as E. coli Nissle 1917 strain (EcN) [38] or Bacillus subtilis [39]. As such, this work constitutes an important methodological improvement in the field of living functional materials and living material foundries, and could have implications for therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…possess high secretory ability and some strains utilize ''cell factories" to produce industrial enzymes (Ruiz-Garcia et al, 2005; Niazi et al, 2014). Several B. subtilis strains can colonize the intestinal microvilli of the animal, support nutrition, and trigger a healthy immune system (Guo et al, 2016, 2017; Abd El-Tawab et al, 2016). Several strains of B. amyloliquefaciens subsp.…”
Section: Genes Involved In Promoting Animal Growthmentioning
confidence: 99%
“…The most commonly used probiotics are Lactobacillus , Bifidobacterium , Bacillus , and yeast strains. Supplemental B. subtilis increases growth performance, disease resistance and immune response in animals (Guo et al, 2016, 2017). Previous reports have demonstrated that Bacillus velezenis QST713 (Pandin et al, 2018), Bacillus velezenis M75 (Kim et al, 2017), and Bacillus velezenis S3-1 (Jin et al, 2017) showed a strong ability to form biofilm and inhibit pathogens.…”
mentioning
confidence: 99%